General and specific immunosuppression caused by antiviral T-cell responses. - Zinkernagel, R; Planz, O; Ehl, S; Battegay, M; Odermatt, B; Klenerman, P; Hengartner, H (1999)
Immunosuppression caused by the non-cytopathic lymphocytic choriomeningitis virus (LCMV) (an RNA virus) is mediated by antiviral cytotoxic T cells that destroy LCMV-infected cells, also of the immune system. While this immunopathological destruction of antigen-presenting cells, macrophages and follicular dendritic cells and of some CD4+ T cells causes general immunosuppression and impairs immune response to third party antigens, it also enhances exhaustion/deletion of LCMV-specific CD8+ T-cell responses. LCMV seems in addition to infect neutralizing antibody-producing B cells via the specific receptor; immunopathological LCMV specific CD8+ T-cell-mediated elimination of these infected B cells (but not of uninfected internal virus antigen-specific B cells) causes a highly specific immunosuppression that delays neutralizing antibody responses and thereby enhances virus persistence. Both generalized and specific immunosuppression by CD8+ T-cell-mediated immunopathology may be involved in human infections with HIV, hepatitis B virus or hepatitis C virus.